Differences in Family Support for Childbirth Preparation Among Pregnant Women in Urban and Rural Areas - Khoula Shofil Hasanah; Emi Lindayani; Ida Nurhidayah (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Childbirth preparation is an important aspect in reducing the risk of pregnancy complications and maternal and infant mortality, with family support playing a role in the physical and psychological readiness and decision-making of pregnant women. Differences in the characteristics of urban and rural areas have the potential to influence the form and level of family support received by pregnant women. This study aims to analyze differences in family support for childbirth preparation among pregnant women in urban and rural areas of Sumedang Regency. Method: A quantitative cross-sectional study was conducted on 210 pregnant women, consisting of 105 respondents from urban areas and 105 respondents from rural areas. The sampling technique used proportionate stratified random sampling. The research instrument was a family support questionnaire covering informational, evaluative, instrumental, and emotional dimensions. Data analysis was performed using the Mann-Whitney U test. Result: The majority of respondents showed good family support, with a higher proportion in urban areas (76.19%) than in rural areas (67.62%). The average value of family support in urban areas was higher than in rural areas. The bivariate test showed a statistically significant difference in family support between the two areas (p <0.05). Conclusion: Regional characteristics influence variations in family support for childbirth preparation among pregnant women.